Who claims the rights to livestock? Exploring gender patterns of asset holdings in smallholder households in Uganda - Hillesland, Marya; Doss, Cheryl; Slavchevska, Vanya (International Food Policy Research Institute, 2021)
This study investigates the gendered patterns of livestock ownership in rural households in Uganda using a detailed data set with information on ownership, management, and decision-making across different types of livestock. Drawing on the bundle of rights frameworks developed by Schlager and Ostrom (1992) and Benjaminsen and Ba (2009), the analysis demonstrates the importance of going beyond considering ownership to also consider these other rights. We find that people may claim to be owners, but not to have the management or fructus rights, but also people may have these latter rights without claiming ownership. Using interviews from both the husband and wife in the household, we analyze the patterns of disagreement regarding claims to these rights and find substantial disagreement.